School Administrators’ Leadership Competencies and Teachers’ Resilience During Covid-19 Pandemic - Hostallero, Michael Ballon; Cabal, Esmen M. (Future Science / FSH-PH Publications, 2024)
This study investigated the relationship between school adminis-trators’ leadership competencies and teachers’ resilience during the COVID-19 pandemic in the Zone 1 Division of Zambales for the school year 2020-2021. Using a descriptive research design, data were gathered from 136 randomly selected principals and teachers through a questionnaire. Results indicated that the school admin-istrators were rated